An overview of the extraction methods of plant-based natural antioxidant compounds / Nur Fadilah Harun and Farah Hanim Ab Hamid - Harun, Nur Fadilah; Ab Hamid, Farah Hanim (Universiti Teknologi MARA, 2021)
Natural antioxidants are widely used in food additives, application in functional foods or also known as ingredients that offer health benefits that extend beyond their nutritional value, and pharmaceutical. These natural antioxidants such as carotenoids, vitamins, and poly phenol can be obtained from fruit, vegetables, and traditional herbal medicines. However, there have several issues regarding the conventional extraction method to extract natural antioxidants compounds from food and medicinal plants such as require a large volume of solvent and long extraction time. Therefore, new green extraction methods such as microwave-assisted, ultrasound-assisted, pulsed electric field, enzyme-assisted, supercritical fluid, and pressurized liquid, technologies were studied to overcome these constraints. Thus, different types of extraction and their mechanism in natural antioxidant compounds extraction was further discussed in this study. Besides, the main classes, source of natural antioxidants and their health benefits also were presented in this paper.